Lepton Mixing Patterns from PSL2(7) with a Generalized CP Symmetry - Shu-Jun Rong (Advances in High Energy Physics)
Lepton mixing patterns from the modular group PSL2(7) with generalized CP symmetries are studied. The residual symmetries in both charged lepton and neutrino sectors are Z2×CP. Seven types of mixing patterns at the 3σ level of the new global fit data are obtained. Among these patterns, three types of patterns can give the Dirac CP phase which is in the 1σ range of the global fit data. The effective mass of neutrinoless double-beta decay for these patterns is also examined.